Iowa Birdline update, August 21, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for August 21, 1989. Highlights include sightings of a Laughing Gull and a Lesser Black-backed Gull. Epson - sheet feed/flatbed